THE URGENCY OF ESTABLISHING A SPECIAL COURT FOR ELECTION DISPUTES REGIONAL HEAD ELECTION DISPUTES IN THE INDONESIAN JUDICIAL SYSTEM - ibnu susilo, Efendi; Taufiqurrahman, Faishal (International Conference On Law And Social Sciences, 2024)
The purpose of this research is first, how is the urgency of special courts in resolving disputes over regional head elections in the judicial system in Indonesia, second, how is the existence and position of special courts in the judicial system in Indonesia. This research uses normative legal research methods, namely research on the norms that apply in resolving disputes over election results, both those contained in local government laws and in other laws and regulations relevant to the object of research. In addition, it also uses comparative, historical and case methods. Special courts in the settlement of election disputes are carried out by forming judicial institutions as executors of judicial power, so that they are included in one of the 4 (four) judicial circles as stipulated in Article 24 of the 1945 Constitution of the Republic of Indonesia and Law Number 48 of 2009 concerning Judicial Power, or by forming special courts for the settlement of election disputes appointed and formed based on laws whose existence is outside the institution of judicial power, meaning that it is separate from the 4 (four) existing judicial circles, even if juris normative is possible